The relationship between vertical stiffness in maximal and submaximal hopping tests and running performance in young middledistance runners: A pilot study - Ryu, J. H.; Murray, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study investigated the relationship between vertical stiffness in the sub-maximal and maximal bilateral hopping test and middle-distance running performance in young middle distance runners. The longer distance running performance was more correlated with normalized vertical stiffness in sub-maximal hopping, Wile the sprint performance was statistically linked to vertical stiffness in maximal hopping. Vertical stiffness measured in combination of the sub-maximal and maximal hopping tests might be utilized as a useful indicator for middle-distance running performance. Accordingly, incorporating plyometric exercises, especially involving vertical motions, might benefit middle-distance running performance.